Providing sustainable, widespread adoption of ACP in care homes. Issue 2 (1st June 2012) - Thomas, K; Stobbart-Rowlands, M; Giles, L
Abstract : The Gold Standards Framework (GSF) Care Homes training and accreditation programme includes ACP as one of the 20 standards. The accreditation process ensures the standards for quality end of life care are embedded and sustained within the care home, evidenced by portfolio, ADA audit and a visit. Evidence from over 2000 care homes trained, 200 accredited and 50 reaccredited after 3 years reveals sustained improvements in EOLC and ACP, showing a positive impact on the quality of care received toward the end of life and reduction on hospitalisation. Staff have managed ACP discussions well and they have direct impact on the reduction of inappropriate crisis hospital admissions toward the end of life. The GSF care homes programme achieves these sustainable improvements through a staged programme that focuses on the whole system within the care home.- use of ACP to clarify needs but other processes to meet them, to ensure care in alignment with preferences. ACP is taught in various ways as part of the training programme- taught theory, role play, 'goldfish bowl', case history, The portfolios of evidence demonstrate attainment of required standards, feedback from relatives and residents, and whole team involvement. If the work is not embraced by the whole team but undertaken as an isolated project, the impact is reduced and the changes are not sustainable. The reaccredited homes have maintained and improved their standards of care and ACP uptake- not just standard practice but enhanced practice- ensuring consistency and continuity